2014
DOI: 10.1016/j.carres.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of 6-deoxy-6-fluorosucrose suitable for PET applications

Abstract: A new route to 6-deoxy-6-fluorosucrose has been developed. The process proceeds in 8 linear steps in 25% overall yield from sucrose. The steps incorporating fluorine and subsequent deprotection are quite rapid, making the procedure useful in the context of F-labeling for PET applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…18 F was produced by the nuclear reaction 18 O(p,n) 18 F using a GE PET Trace cyclotron as described (Rotsch et al, 2015). The precursors (6'-O-Trifluoromethanesulfonyl-2,3,4,6,1',3',4'hepta-O-benzoylsucrose for 6'-[ 18 F]FDS; 1'-O-Trifluoromethanesulfonyl-2,3,4,6,3',4',6'-hepta-O-benzoylsucrose for 1'-[ 18 F]FDS; and 6-O-Trifluoromethanesulfonyl-2,3,4,1',3',4',6'-hepta-Obenzoylsucrose for 6-[ 18 F]FDS ) were prepared as described (Gaddam and Harmata, 2013;Ying et al, 2013;Gao et al, 2014).…”
Section: Radiosynthesis Of [ 18 F]fds Analogsmentioning
confidence: 99%
“…18 F was produced by the nuclear reaction 18 O(p,n) 18 F using a GE PET Trace cyclotron as described (Rotsch et al, 2015). The precursors (6'-O-Trifluoromethanesulfonyl-2,3,4,6,1',3',4'hepta-O-benzoylsucrose for 6'-[ 18 F]FDS; 1'-O-Trifluoromethanesulfonyl-2,3,4,6,3',4',6'-hepta-O-benzoylsucrose for 1'-[ 18 F]FDS; and 6-O-Trifluoromethanesulfonyl-2,3,4,1',3',4',6'-hepta-Obenzoylsucrose for 6-[ 18 F]FDS ) were prepared as described (Gaddam and Harmata, 2013;Ying et al, 2013;Gao et al, 2014).…”
Section: Radiosynthesis Of [ 18 F]fds Analogsmentioning
confidence: 99%
“…The enzymatic approach was recently applied to obtain the first 18 F fluorinated derivative, 1’-[ 18 F]fluoro-1’-deoxysucrose, in 26% yield [ 39 ]. We have recently reported the first purely synthetic approaches for the syntheses of 6’-deoxy-6’-fluorosucrose, 1’-deoxy-1’-fluorosucrose, and 6-deoxy-6-fluorosucrose [ 42 44 ]. Here, we report the first radiolabeling of sucrose with 18 F at the 6’ position, and the utility of 6’-deoxy-6’[ 18 F]fluorosucrose ( 18 FS) in studying sucrose phloem transport in maize ( Zea mays ) leaves and specifically with sucrose transporter (SUT) proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of 6-deoxy-6-fluorosucrose (6-F-sucrose) was reported by Eklund and Robyt ( Eklund and Robyt, 1988 ). Recently, a new route to 6-F-sucrose synthesis has been developed by Gao et al (2014) . Authors also proposed its application in plant imaging using PET ( Gao et al, 2014 ).…”
Section: Questions and Considerations In Future Fdg Experimentsmentioning
confidence: 99%
“…Recently, a new route to 6-F-sucrose synthesis has been developed by Gao et al (2014) . Authors also proposed its application in plant imaging using PET ( Gao et al, 2014 ). Rotsch et al (2015) subsequently demonstrated that 6-F-sucrose translocation closely resembles 14 C-sucrose translocation in maize leaves.…”
Section: Questions and Considerations In Future Fdg Experimentsmentioning
confidence: 99%